Exploring Playful Learning: Development of Interactive Game using Block Calculator - Santos, Ciro (2023)
Games have great educational potential and attract people due to the interactivity they provide.Using playful elements in education can be promising, especially considering that the new generation grows up immersed in the digital world, acquiring skills naturally when interacting with technological devices.Technology can be an important ally to bring teaching closer to playfulness, allowing the time spent on electronic devices to generate positive results in education.In this sense, an educational game was developed for the Android platform, using the LUA programming language, the Corona SDK emulator and the Sublime Text text editor.The objective of the application is to help teach Mathematics through the block calculator, stimulating cognitive and social aspects, making studying a pleasant moment through challenges that encourage discovery and creating a pleasant study environment conducive to learning.   Keywords: Educational game. Games applied in teaching mathematics. Android. Lua. Corona SDK.